Experimental topographic and anatomical substantiation of hybrid osteosynthesis of the fibula in patients with ankle fractures - Vladimir O. Tsapenko; Yuri B. Kashansky; Igor P. Kondratyev; Anatoly V. Polikarpov; Rostislav V. Vashetko (Гений oртопедии)
Introduction Ankle fractures are one of the common injuries treated by orthopaedic surgeons. The lack of a standard medical care can be associated with poor outcomes, high disability rates with conservative treatments. Reported outcomes following operative fixation vary widely in the literature and infectious complications can complicate the rehabilitation process. The objective was to show a clinical possibility, safety and feasibility of a new method of fibula fixation in ankle fractures using necropsy material and to reduce negative consequences after surgical treatment. Material and methods Major vessels and nerves were isolated in the lower third of tibia in 11 biomannequins, AO 44C1 and 44C2 fractures obtained mechanically and fibula fixed using the technique offered. Forces were applied to the injury site through mechanical stress tests. Results The fixation method did not lead to a conflict between fixing screws and major vessels and nerves. No visible changes in the fibula position were noted in the biomannequins with the foot brought to extreme positions of plantar and dorsal flexion, with stress tests causing valgus and varus deformities. Discussion As opposed to conventional surgical treatments of ankle fractures, no large incisions are required with the technique to place implants. There is no need to use plates, and the fracture can be fixed using the paired bone of the injured segment instead. Fixation screws can be inserted transcutaneously through soft tissue punctures. The new method is associated with less trauma, less quantity of metal needed and reduced probability of infectious complications. It can be used for AO 44C1 and 44C2 fractures in medical institutions with different availability of equipment. Conclusions Ankle fractures can be repaired with the technique offered causing no damage to the major vessels and nerves at the surgical site. Stress tests showed stable fibula fixation achieved in all cases avoiding mobility at the fracture site. The new technique can facilitate normal reparative osteogenesis in clinical practice.